2019
DOI: 10.7595/management.fon.2019.0014
|View full text |Cite
|
Sign up to set email alerts
|

Organizational innovativeness: factors that drive innovations in social enterprises in Serbia

Abstract: Research Question: This paper explores factors that drive innovativeness of social enterprises in Serbia. Motivation: Social enterprises are gaining importance on global scale, being recognized for their potential to respond to both economic and social challenges, attract capital and generate income in non-traditional ways. Innovativeness comes at the hart of their abilities to achieve their goals. This research is motivated by the idea to understand which factors influence innovativeness in Serbian social ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It is a significant challenge to develop a comprehensive framework for strategically managed scientific and research work in SROs. There is a consensus in the literature that organisational innovativeness is crucial for long-term sustainability [66]. According to the literature, we incorporated the strategic and project management components in our model [63], [98] to examine their influence on an innovative organisational design.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…It is a significant challenge to develop a comprehensive framework for strategically managed scientific and research work in SROs. There is a consensus in the literature that organisational innovativeness is crucial for long-term sustainability [66]. According to the literature, we incorporated the strategic and project management components in our model [63], [98] to examine their influence on an innovative organisational design.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…In the literature review, as part of creating the so-called hierarchical model of corporate entrepreneurship maturity, Vučković et al (2017) highlight the following factors as key to the effectiveness of this process: organizational culture (promoting innovativeness at all levels of the organization, participatory leadership, risk taking and work motivation), organizational infrastructure (includes the flat organizational structure, then clear and concrete policies, strategies, plans and procedures for innovation management in the organization, and finally the simple and clear communication channels for information exchange within innovation management), organizational resources and abilities (sufficient human, material and financial resources, necessary for the implementation of new ideas in the organization). When it comes to research on this topic in Serbia, Miric et al (2019) conducted a study of factors affecting organizational innovativeness in social enterprises in Serbia. They concluded that some of the most important factors in this regard are awareness of the enterprise's social mission, perception of innovation as important, orientation towards growth, motivation to work, professional life satisfaction, etc.…”
Section: Literature Reviewmentioning
confidence: 99%